2017
DOI: 10.1051/ijmqe/2017006
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of low-cost, single-frequency GNSS receivers to standards consistent with ISO for control surveying

Abstract: Abstract. The emergence of single-frequency, navigation-type Global Navigation Satellite System receivers capable to provide carrier phase data [the so-called high sensitivity (HS) carrier phase positioning] has been steadily growing over the recent years. The main purpose of this study is to metrologically evaluate two low-cost, HS receivers, namely the u-blox LEA-6T and NEO-7P, in control surveying specifications. The evaluation was carried out within a published framework of standards and associated guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
1
20
0
6
Order By: Relevance
“…A GNSS survey isconsidered to be qualified for its purpose when it is delivered withsufficient reliability [16]. Therefore, using low‐cost single‐frequency receivers for RTK, there is aneed to ensure that the receiver can meet standards that guarantee areliable geodetic control work [34].…”
Section: Qualitative Performance Analysis Of Cs Resolution Scheme Fmentioning
confidence: 99%
“…A GNSS survey isconsidered to be qualified for its purpose when it is delivered withsufficient reliability [16]. Therefore, using low‐cost single‐frequency receivers for RTK, there is aneed to ensure that the receiver can meet standards that guarantee areliable geodetic control work [34].…”
Section: Qualitative Performance Analysis Of Cs Resolution Scheme Fmentioning
confidence: 99%
“…As the pseudo-range and Doppler measurements are usually used in the GNSS vehicle navigation system, the high-end and expensive systems can achieve real-time positioning accuracy of less than 3 m. However, the cost is too high for ordinary vehicles which only need a primary navigation module [ 2 , 3 ]. With the evolution of GNSSs, there are increasingly systems and enhancement algorithms for positioning technology available, and the positioning accuracy of low-cost, single-frequency GNSS receivers has been improved to a certain extent [ 7 ]. We can obtain a 4–6 cm accuracy level in real-time stand-alone positioning if a CORSs network is used [ 4 , 5 , 8 ].…”
Section: Related Workmentioning
confidence: 99%
“…Geodetic GNSS instruments are able to measure code and phase pseudo-ranges with high accuracy and precision that indicates better performance [11]. However, they are argued as too expensive in certain applications and, therefore, low-cost GNSS instruments may be seen as a suitable alternative [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Geodetic GNSS instruments were used as a reference to test low-cost instruments in dynamic and static scenarios, and the results indicated that, in certain applications, low-cost instruments can have satisfactory performance that is comparable with geodetic instruments [ 18 , 19 ]. Geodetic as well as single-frequency low-cost GNSS receivers were tested in Real-Time Kinematic (RTK) mode following the International Organization for Standardization (ISO) standard 17123-8.…”
Section: Introductionmentioning
confidence: 99%